A new classification for pterygomaxillary implants and its related surgical implications: a retrospective cohort study - Jie Ren; Ling Shu (BMC, 2024)
Abstract Background To provide a novel classification for all implants in the maxillary retromolar region to simplify surgical design, reduce surgical risks, and guide clinicians in clinical decision-making. Methods A total of 180 patients with bilateral partial or completely edentulous atrophic posterior maxillae who had received or were scheduled to receive pterygomaxillary implants were included in this study. Cone-beam computed tomography was performed, and the sagittal and coronal images were acquired at 110 kV and 10 mA. The exposure volume was 120 mm in diameter and 80 mm in height. The pterygomaxillary implants were divided into three different types based on the anatomical structures the implants passed through. Results The average age of the 180 patients was 69 (range: 39-89) years; 99 were men and 81 were women. All the patients exhibited 360 pterygomaxillary implant sites. However, during mimic implantation, 14 implant sites were excluded due to severe resorption of the tuberosity, very small pterygoid plates, or variations in the descending palatal artery configuration. Of the 346 pterygomaxillary implant sites, 24.0% (83/346), 40.7% (141/346), 22.0% (76/346), and 13.3% (46/346) were classified as Types I, IIa, IIb, and III, respectively. Conclusions Type II pterygomaxillary implants were the most commonly used in the novel classification. Different types of pterygomaxillary implants should follow specific designs and surgical strategies to achieve optimal outcomes.